Are CSR communication initiatives effective in social media? : examining the case of the fast fashion industry - Viana, Maria Carolina Miranda Cardoso de Abrantes (2020)
Fast fashion clothing brands increasingly rely on social media platforms to interact with consumers and share their new collections, as well as their corporate social responsibility activities. Meanwhile, according to recent research, consumers are increasingly more prone to purchase from socially responsible companies and tend to avoid those that are not so socially responsible. The present research aims to build on current academic literature and examines the impact of social media posts focused on corporate social responsibility by fast fashion brands on consumer behaviour, particularly consumers’ purchase intention and online brand engagement. In order to evaluate that, an experiment was implemented with three different scenarios of Instagram posts being created. Two types of corporate social responsibility (social causes and environmental issues) were compared with a control group (regular brand posts). In total, 302 valid responses were obtained in a survey targeted exclusively to Instagram users. Results indicate that both types of corporate social responsibility have a positive impact on consumers’ purchase intention and online brand engagement compared to the control group. Furthermore, findings also suggest that women and older individuals reveal significantly higher purchase intention and online brand engagement than men and younger individuals. The conclusions obtained are mostly consistent with the literature. Theoretical and managerial implications of the findings are also discussed, reinforcing the relevance of this study.